Connection of the Ukrainian decorative ornament with folk beliefs and representations - O.A. Рolovna-Vasileva (Academy of Cognitive and Natural Sciences, 2006)
In this article research of connection of the Ukrainian decorative ornament with folk beliefs and representations, an icon graphic specificity, synonymic names, and contents value is sent.